2022
DOI: 10.1039/d1fo03085j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-amylosestarch branching enzyme IIwheat mutants on starch digestibility in bread, product quality, postprandial satiety and glycaemic response

Abstract: Impact of white bread made from sbeII wheat flour on postprandial glycaemic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…According to this classification system, further confirmed by Atkinson et al [ 36 ], the fresh pasta enriched with 50 to 100% high-amylose wheat flour exhibited practically the same in vitro glycemic index of circa 43% at a confidence level of 95%, and thus would fall within the range of low-in-vitro-GI foods; these foods induce a small increase in the post-meal level of glucose in the blood and therefore lower the long-term risk of type 2 diabetes mellitus on top of preventing obesity and metabolic risk factors such as coronary heart disease [ 37 ]. These results agree with previous studies carried out on other high-amylose foods, such as rusks [ 10 ], bread [ 8 , 38 , 39 , 40 ], pasta [ 11 ], noodles [ 6 ], and semolina pudding [ 41 ].…”
Section: Resultssupporting
confidence: 92%
“…According to this classification system, further confirmed by Atkinson et al [ 36 ], the fresh pasta enriched with 50 to 100% high-amylose wheat flour exhibited practically the same in vitro glycemic index of circa 43% at a confidence level of 95%, and thus would fall within the range of low-in-vitro-GI foods; these foods induce a small increase in the post-meal level of glucose in the blood and therefore lower the long-term risk of type 2 diabetes mellitus on top of preventing obesity and metabolic risk factors such as coronary heart disease [ 37 ]. These results agree with previous studies carried out on other high-amylose foods, such as rusks [ 10 ], bread [ 8 , 38 , 39 , 40 ], pasta [ 11 ], noodles [ 6 ], and semolina pudding [ 41 ].…”
Section: Resultssupporting
confidence: 92%
“…The single enzyme assay used to determine starch digestibility here is a sensitive method and may be able to detect subtle differences compared to the RS AOAC method by producing several experimental parameters to characterise the digestibility curves providing accurate estimates of digestion. The percentage of starch hydrolysed by α-amylase, as reported in this study (C 90 ), has been shown to correlate well with glycaemic index measurements in human participants (Edwards C.H., et al, 2019), suggesting that the lower starch digestibility of sbeII starch in bread has potential for applications in frozen bread, as shown by a previous study (Corrado M., et al, 2022), but also when bread is consumed fresh, or after storage in the fridge or at room temperature.…”
Section: Discussionsupporting
confidence: 85%
“…Bread rolls were baked from sbeII and WT flours as described previously (Corrado M., et al, 2022) to achieve a similar starch content ( ~ 75 g) based on the total starch content of the flour. The same process as used to produce sbeII and WT control doughs, later portioned into rolls and baked.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations